Advanced fibrosis of non-alcoholic steatohepatitis affects the significance of lipoprotein(a) as a cardiovascular risk factor. (April 2020) - Konishi, Kanako; Miyake, Teruki; Furukawa, Shinya; Senba, Hidenori; Kanzaki, Sayaka; Nakaguchi, Hironobu; Yukimoto, Atsushi; Nakamura, Yoshiko; Watanabe, Takao; Koizumi, Yohei; Yoshida, Osamu; Tokumoto, Yoshio; et al.
Abstract: Background and aims: Lipoprotein(a) [Lp(a)] is an important independent cardiovascular risk factor. However, Lp(a) levels are lower in patients with chronic liver disease than in healthy subjects. Furthermore, Lp(a) levels decrease as residual liver function declines. Although non-alcoholic fatty liver disease (NAFLD), especially advanced non-alcoholic steatohepatitis (NASH), increases the risk of cardiovascular diseases, the relationship between serum Lp(a) level and NASH is unknown. Thus, we examined the relationship between serum Lp(a) levels and biopsy-proved NAFLD and clarified the significance of Lp(a) measurements for cardiovascular disease screening in patients with NAFLD. Methods: A total of 176 patients with NAFLD were enrolled. Comprehensive blood chemistry tests and histological examinations of liver samples were conducted. The relationship between serum Lp(a) levels and NAFLD was analyzed. Results: Serum Lp(a) levels in advanced fibrosis (stage 3–4) were lower than those in non-advanced fibrosis (stage 0–2) ( p  < 0.05). After adjustment for age, sex, body mass index, alanine aminotransferase (ALT), creatinine (Cre), HbA1c level, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), and the use of lipid-lowering agents, the significant inverse association between advanced fibrosis and serum Lp(a) levels remained ( p  < 0.01). Although the Lp(a) level was inversely associated with an NAFLD Activity Score (NAS) of 5–8, there was no significant association between Lp(a) levels and NAS adjusted for age, sex, body mass index, ALT, Cre, HbA1c level, HDL-C, LDL-C, TG, and the use of lipid-lowering agents. Conclusions: Advanced NASH is associated with low serum Lp(a) levels; therefore, Lp(a) levels may not be useful in evaluating cardiovascular risk. Graphical abstract: Image 1 Highlights: Non-alcoholic fatty liver disease (NAFLD), especially advanced non-alcoholic steatohepatitis (NASH), is closely related to cardiovascular disease. Advanced NASH is associated with low serum Lp(a) levels. Lp(a) levels in advanced NASH may not be useful in evaluating cardiovascular risk.